2014
DOI: 10.1089/soro.2013.0002
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Combining Hard and Soft Robots

Abstract: This manuscript describes a hybrid robotic system combining hard and soft sub-systems. This hybrid comprises a wheeled robot (an iRobot Create©; hard) and a four-legged quadruped (soft).It is capable (using a simple, wireless control system) of rapid locomotion over flat terrain (using the wheeled hard robot), and of gripping and retrieval of an object (using the soft robot). The utility of this system is demonstrated by performing a mission requiring the capabilities of both components: retrieving an object (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
111
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 214 publications
(113 citation statements)
references
References 29 publications
0
111
0
2
Order By: Relevance
“…1.2 kg 10 ), tethers greatly simplify system design by significantly reducing the required carrying capacity. One approach to achieving mobile systems is to tether a soft robot to a mobile rigid robot with a greater carrying capacity 89 . Untethered mobile systems have circumvented the challenge of carrying heavy power sources by operating underwater 11, 31 or rolling on a surface 28,8 such that actuation system masses do not have to be lifted against gravity.…”
Section: Locomotionmentioning
confidence: 99%
See 1 more Smart Citation
“…1.2 kg 10 ), tethers greatly simplify system design by significantly reducing the required carrying capacity. One approach to achieving mobile systems is to tether a soft robot to a mobile rigid robot with a greater carrying capacity 89 . Untethered mobile systems have circumvented the challenge of carrying heavy power sources by operating underwater 11, 31 or rolling on a surface 28,8 such that actuation system masses do not have to be lifted against gravity.…”
Section: Locomotionmentioning
confidence: 99%
“…10 , e) worm-inspired locomotion 88 , f) particle jamming-based actuation 42 , g) rolling powered by a pneumatic battery 28, h) a hybrid hard/soft robot 89 , i) snakeinspired locomotion 8 , j) jumping powered by internal combustion 58 , k) manta-ray inspired locomotion 100 , and l) an autonomous fish 11 . Grasping and manipulation, canonical challenges in robotics, can be greatly simplified with soft robotics.…”
Section: Martinez R V Et Al Robotic Tentacles With Three-dimensiomentioning
confidence: 99%
“…This idea was demonstrated in our previous work, Stokes et al (2014), where we showed that the advantages of speed and accuracy offered by hard robotics could be combined with the versatility of soft robotics. We use a similar design strategy here, for a pick and place task.…”
mentioning
confidence: 83%
“…The advantages of integrating soft robotic components with other types of robotic systems is demonstrated by their use in haptic classification (used in combination with a Baxter robot) (Homberg et al, 2015) and in object retrieval (used in combination with a Roomba wheeled-hard robot) (Stokes et al, 2014). These two examples are hybrids and share many common system components, but the system designers used their own bespoke control systems.…”
mentioning
confidence: 99%
“…This paper describes the modular assembly of hybrid [29] reconfigurable robots/machines using magnets. Although non-magnetic, modular assembly of soft robotic snakes has been explored by Onal et al, the reconfigurability of the reported robots has not been demonstrated.…”
Section: Introductionmentioning
confidence: 99%